2009
DOI: 10.1002/ijc.24183
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA expression in urothelial carcinomas: Important roles of miR‐10a, miR‐222, miR‐125b, miR‐7 and miR‐452 for tumor stage and metastasis, and frequent homozygous losses of miR‐31

Abstract: We analyzed 34 cases of urothelial carcinomas by miRNA, mRNA and genomic profiling. Unsupervised hierarchical clustering using expression information for 300 miRNAs produced 3 major clusters of tumors corresponding to Ta, T1 and T2-T3 tumors, respectively. A subsequent SAM analysis identified 51 miRNAs that discriminated the 3 pathological subtypes. A score based on the expression levels of the 51 miRNAs, identified muscle invasive tumors with high precision and sensitivity. MiRNAs showing high expression in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
142
0
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(164 citation statements)
references
References 50 publications
15
142
0
7
Order By: Relevance
“…20 In our study, preferential adhesion of HEC1A cells to fibronectin and laminin can be accounted by the binding of cell surface molecules with these 2 ECM proteins as an initial step of cancer cell invasion and metastasis. 21,22 Taken together, our results implied that miR-7, miR-194 and miR449b knockdown and miR-204 induction may suppress cell motility by hindering adhesion to fibronectin-/lamininbearing surfaces.…”
Section: Cancer Cell Biologymentioning
confidence: 70%
See 1 more Smart Citation
“…20 In our study, preferential adhesion of HEC1A cells to fibronectin and laminin can be accounted by the binding of cell surface molecules with these 2 ECM proteins as an initial step of cancer cell invasion and metastasis. 21,22 Taken together, our results implied that miR-7, miR-194 and miR449b knockdown and miR-204 induction may suppress cell motility by hindering adhesion to fibronectin-/lamininbearing surfaces.…”
Section: Cancer Cell Biologymentioning
confidence: 70%
“…MicroRNAs (miRNAs) are small noncoding RNA molecules of [19][20][21][22][23][24] nucleotides that regulate gene expression posttranscriptionally through imperfect base pairing with the 3 0 -untranslated region (3 0 UTR) of target mRNAs, causing transcript degradation and translational inhibition. 3 Approximately 20-30% of all genes are targeted by miRNAs and a single miRNA may target as many as 200 genes.…”
mentioning
confidence: 99%
“…They are identical at nucleotides 2-8, which seems to be the most important segment for target recognition (51). miR10a has been studied in several tumors (52)(53)(54). According to TargetScan4.0 analysis, the KLF4 mRNA target site for miR10b overlaps with miR-10a.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, homozygous loss of the miR-31-encoding genomic locus has been described in human urothelial carcinoma 33 and acute lymphoblastic lymphoma. 34 On the other hand, several studies showed that miR-31 is upregulated in colorectal cancer, hepatocellular cancer and most squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%